Spontaneous Bacterial Peritonitis due to Lactobacillus paracasei in Cirrhosis - Emily Harding-Theobald; Bharat Maraj (Case Reports in Gastrointestinal Medicine)
Lactobacillus species colonize the human gastrointestinal tract and are rarely pathogenic. We present a case involving a cirrhotic patient who presented with sepsis and was found to have peritoneal cultures demonstrating Lactobacillus as the sole pathogen concerning for spontaneous bacterial peritonitis. Treatment was achieved with high-dose penicillin and clindamycin but the patient developed hepatorenal syndrome and died from acute renal failure. Intra-abdominal Lactobacillus infections are typically seen in patients undergoing peritoneal dialysis or who have recently had bowel perforation. There are few case reports of spontaneous Lactobacillus peritonitis in patients with cirrhosis. Our case report addresses the challenges of Lactobacillus treatment and suggests antibiotic coverage of commensal organisms in patients who do not improve with standard management.